2011
DOI: 10.1007/s00702-011-0601-1
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of complex regional pain syndrome: not a random process

Abstract: Complex regional pain syndrome (CRPS) generally remains restricted to one limb but occasionally may spread to other limbs. Knowledge of the spreading pattern of CRPS may lead to hypotheses about underlying mechanisms but to date little is known about this process. The objective is to study patterns of spread of CRPS from a first to a second limb and the factors associated with this process. One hundred and eighty-five CRPS patients were retrospectively evaluated. Cox’s proportional hazards model was used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 41 publications
4
79
0
Order By: Relevance
“…Female gender can be considered a risk factor for CRPS [15,[18][19][20][23][24][25][26] and, since there is a higher incidence in older patients, the postmenopausal status is also related higher incidence of CRPS [14][15][16]21], although this association could be an epiphenomena linked to higher incidence of fractures and others traumas in this population. However, the common factor in many of these risks may be nerve entrapment.…”
Section: Risk Factorsmentioning
confidence: 83%
“…Female gender can be considered a risk factor for CRPS [15,[18][19][20][23][24][25][26] and, since there is a higher incidence in older patients, the postmenopausal status is also related higher incidence of CRPS [14][15][16]21], although this association could be an epiphenomena linked to higher incidence of fractures and others traumas in this population. However, the common factor in many of these risks may be nerve entrapment.…”
Section: Risk Factorsmentioning
confidence: 83%
“…The pattern of spread is initially on a single limb from distal to proximal but in some people CRPS can progress to involve the contralateral or ipsilateral limb/s. A younger age at onset and more severe CRPS are both risk factors for an increased chance of spread, with a contralateral pattern of spread the most common form (Van Rijn et al 2011). …”
Section: Altered Sensory Perceptionsmentioning
confidence: 99%
“…The syndrome is characterized by continuous regional pain, which is disproportionate according to duration and intensity, depending on the type of the initial damage (1). It has been observed that the progression of the disease induces spontaneous spread of symptoms along the affected extremity (5). CRPS type I is manifested in cases where pain is not limited to a dermatome or peripheral nerve distribution, while CRPS type II refers to cases where a nerve lesion is present (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that changes in the peripheral and central somatosensory and autonomous nervous system, as well as neurogenic inflammation, lead to the manifestation of CRPS I (3,5,6).…”
Section: Introductionmentioning
confidence: 99%